ANALISIS EFISIENSI DAN EFEKTIVITAS PENGELOLAAN ANGGARAN DANA DESA DI DESA TAMBAK BITIN KABUPATEN HULU SUNGAI SELATAN TAHUN 2016-2017 - MUTHIA NOR FITRIANI; SAIPUDIN SAIPUDIN (PPJP Universitas Lambung Mangkurat, 2019)
This research was conducted (1) for local governments to analyze the effective value of village fund budgets managed for community empowerment and development. (2) for the community, which is to know good results regarding village economic growth, regional and effective village fund centers (3) as a reference for further research on the management of village funds for the empowerment and development of rural communities.The scope of this study is to analyze the efficiency and effectiveness of managing village budget funds for 2016-2017 in the Tambak Bitin village of Hulu Sungai Selatan Regency. The data analysis technique used in descriptive research is collecting, dividing, exposing and deciphering data, so the objective results of the problem are obtained from an analysis of the results of monitoring data. This research also uses quantitative analysis and the result is a percentage. The results of this study are that the efficiency of village funds in Tambak Bitin village is in the inefficient category, this is because village infrastructure is inadequate and population density is high. The level of effectiveness of funds in Tambak Bitin village is included in the category of very effective and effective, influenced by the success of the village government in regulating village income and prioritizing community needs and services provided and felt by the community.Keywords: Efficiency Analysis, Effectiveness, Village Fund Budget